Scan&go conceptual digital business model: qr-code vending machine - Chowdhury, Asif Mahmud; Mehran, Mujib; Al-Mohamadi, Abrar Salah Mohammed; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2020)
The objective of the paper is to propose and introduce a system, a mobile application-based platform called "Scan&Go”, enables the user who have problems in paying cash while using vending machines. Furthermore, "Scan&Go" aims to accomplish part of the Sustainable Development Goal 8 i.e. Decent Work and Economic Growth. The system will provide a connecting digital platform between donor & B40 people, where donors will be able to donate directly to the B40 people. The Design Thinking methodology is adapted for this paper which is to understand the key problems, ideation of possible solution options, validation of options by customer segments, and to suggest a conceptual solution. This includes conducting literature review and benchmark, conducting interviews using the business modeling tools i.e. the nine blocks of Business Model Canvas (BMC), Value Proposition Canvas (VPC), Environment Map (EM), and Strategy Canvas. In this paper, also we presented our literature review findings, as well as proposal of Business Model for Scan&Go – in the of Business Model Canvas (BMC), Value Proposition Canvas (VPC), Environment Map, and strategy canvas. Survey with potential customers has been made to validate the initial BMC/VPC. This paper offers a validated conceptual business model of a digital platform/ apps, called Scan&Go, with focus on improving the experience of vending machine consumers in making cash-less transactions anywhere anytime for the purchasing of coffee or other convenience goods.